Vermicompost Amendment in Soil Affects Growth and Physiology of Zea mays Plants and Decreases Pb Accumulation in Tissues - Zaiga Landorfa-Svalbe; Māra Vikmane; Gederts Ievinsh (Agriculture, 2022)
Minimization of the possible harmful effects of soil pollution on agricultural production and food safety are the major challenges in modern agriculture. There is great scientific interest in the detailed understanding of the physiology of lead uptake and toxicity in Zea mays, together with the search for approaches to minimizing Pb accumulation in tissues. The aim of the present study was to explore the possibility of reducing Pb accumulation in Z. mays plants cultivated in Pb-contaminated soil, by means of vermicompost amendment. Z. mays plants were cultivated at three soil vermicompost amendment rates (10, 20, and 30%), with the addition of 1000 mg L−1 of Pb in the form of Pb(NO3)2 or an equivalent amount of nitrogen in the form of NH4NO3. Additional nitrogen had a significant stimulatory effect on plant growth and physiology, but only for control plants, and at a low vermicompost amendment rate. Independently, Pb had an insignificant negative effect on plant growth and biomass partitioning, but significantly negatively affected the mineral nutrition of Z. mays plants. At a 10 and 20% soil vermicompost amendment rate, the Pb concentration in plant leaves and roots decreased by 65%, while plant biomass increased four to five times in comparison to soil-grown control plants, together with accelerated flowering. It was concluded that vermicompost is one of the most promising soil amendments for reducing heavy metal uptake and accumulation in crop plants, while also being an efficient organic fertilizer.